Mammalian Paleoecology Using the Past to Study the Present - Smith, Felisa A. (Book collections on Project MUSE., 2021)
"This book provides an overview of how we obtain information from long-dead mammals and explains what this information can tell us of relevance to ongoing pressing environmental issues"--